Regional developments [in 2020 Global Food Policy Report] - Badiane, Ousmane; Collins, Julia; Makombe, Tsitsi; Abdelaziz, Fatma; Breisinger, Clemens; Khouri, Nadim; Thurlow, James; Akramov, Kamiljon T.; Romashkin, Roman; Park, Allen; Ilyasov, Jarilkasin; Rashid, Shahidur; et al. (International Food Policy Research Institute, 2020)
BUILDING INCLUSIVE FOOD SYSTEMS TO HELP REACH THE GOAL OF ENDING HUNGER and malnutrition globally will require innovation and investment at the regional and country levels. This section discusses problems, policies, and prospects for regional and national food systems in 2020 and beyond across the major regions: Africa, the Middle East and North Africa, Central Asia, South Asia, East and Southeast Asia, and Latin America and the Caribbean. The challenges and potential of inclusion to transform food systems for better well-being and nutrition are examined for each region, along with other current topics